(untitled) (Global Journal of Computer Science and Technology, 2014)
Cloud Computing is one of the latest developments in the IT industry which offers on-demand services without requiring to create an IT infrastructure. It provides scalability, high performance and relatively low cost feasible solution for organizations. Despite of all its advantages, security is still a critical challenge in cloud computing paradigm. This paper presents a survey on some possible techniques used for encrypting user data and also providing techniques used in improving virtualization security for the cloud infrastructure.